Endovascular Rescue of a Narrowed Aorto-Aortic Bypass Graft in a Patient with Takayasu’s Arteritis - Son, Kuk Hui (Korean J Thorac Cardiovasc Surg, 2014)
We report a case of successful endovascular treatment of a pseudoaneurysm and the obstruction of an aorto-aortic bypass graft, which had been performed to treat Takayasu’s arteritis fifteen years prior, at the thoracic aorta. Along with the immediate relief of proximal hypertension that had caused severe heart failure, the successful exclusion of the pseudoaneurysm and the patency of the stem graft were maintained three years after the procedure.